In vitro effects of propolis on Giardia duodenalis trophozoites - Freitas, S. F.; Shinohara, L.; Sforcin, J. M.; Guimaraes, S. (Elsevier B.V., 2006)
In order to improve the current chemotherapy of Giardia infection, potential antigiardial agents have been screened, including natural products. Propolis, a resinous hive product collected by bees, has attracted attention as a useful and popular substance with several therapeutic activities. The present study was carried out aiming to evaluate the in vitro effects of an ethanolic extract of propolis on the growth and adherence of Giardia duodenalis trophozoites. Propolis inhibited the growth of trophozoites and the level of inhibition varied according to the extract concentration and incubation times. The highest reduction of parasite growth was observed in cultures exposed to 125, 250 and 500 mu g/ml of propolis, in all incubation periods (24, 48, 72 and 96 h). Growth reduction by 50% was observed in 125 mu g/ml propolis-treated cultures, while the concentrations of 250 and 500 mu g/ml were able to inhibit growth by more than 60%. Propolis also inhibited parasite adherence and all assayed propolis concentrations promoted the detachment of trophozoites. Light microscope observations revealed changes of the pear-shaped aspect of the cell and reduction of flagellar beating frequency in the great part of the trophozoites. Our results hold the perspective for the utilization of propolis as an antigiardial agent. (c) 2005 Elsevier GmbH. All rights reserved.
Keywords: Giardia duodenalis; propolis; trophozoites; growth; adherence